2006
DOI: 10.1097/01.qai.0000233310.90484.16
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in the Highly Active Antiretroviral Therapy Era

Abstract: Although overall death rates remained low through 2004, the proportion of deaths attributable to non-AIDS diseases increased and prominently included hepatic, cardiovascular, and pulmonary diseases, as well as non-AIDS malignancies. Longer time spent receiving HAART and higher CD4 cell counts at HAART initiation were associated with death from non-AIDS causes. CD4 cell count at time of death increased over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
357
3
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,217 publications
(391 citation statements)
references
References 28 publications
(8 reference statements)
11
357
3
6
Order By: Relevance
“…We then categorized eGFR (<30, 30-45, 45-60, 60-80, >80 mL/min/1.73m 2 ) using the MDRD equation stratified by race, and then repeated the categories using the MDRD-RCR. Next, we compared baseline clinical characteristics of Blacks, stratified by eGFR category: <60, 60-72, and >72 mL/min/1.73m 2 . We specifically distinguished the 60-72mL/ min/1.73m 2 category, as these Blacks are the ones re-classified to eGFR<60 mL/ min/1.73m 2 when the race coefficient is removed from the MDRD equation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We then categorized eGFR (<30, 30-45, 45-60, 60-80, >80 mL/min/1.73m 2 ) using the MDRD equation stratified by race, and then repeated the categories using the MDRD-RCR. Next, we compared baseline clinical characteristics of Blacks, stratified by eGFR category: <60, 60-72, and >72 mL/min/1.73m 2 . We specifically distinguished the 60-72mL/ min/1.73m 2 category, as these Blacks are the ones re-classified to eGFR<60 mL/ min/1.73m 2 when the race coefficient is removed from the MDRD equation.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Recent studies have shown a large disparity in prevalence and incidence of end stage renal disease (ESRD) by race among persons with HIV. [3][4][5] Despite Blacks with HIV-infection having a higher incidence of ESRD and higher prevalence of known CKD risk factors compared with Whites, 4,[6][7][8][9][10] the prevalence of reduced estimated glomerular filtration rate (eGFR <60 mL/min/1.73m 2 ) is similar between Whites and Blacks with HIV. 11 One possible explanation for this observation is that Blacks with HIV may have rapidly progressive CKD leading to a lower prevalence of mildly reduced GFR among Blacks.…”
Section: Introductionmentioning
confidence: 99%
“…However, while there has been a marked reduction in HIV-related mortality and morbidity [2,3], additional challenges have emerged in the long-term management of HIV, such as drug toxicities [4-6], treatment failure due to poor adherence [7,8] and/or drug resistance [9] requiring regimen change, and increasing non-HIV-related morbidity and mortality [10-12]. As with any chronic illness, HIV patients require long-term, regular clinical follow up to monitor disease progression and optimal timing of initiation of HAART, assess response and adherence to antiretroviral therapy and associated adverse events, and address sexual health and HIV prevention needs [13].…”
Section: Introductionmentioning
confidence: 99%
“…En el manejo a largo plazo del paciente con HIV, han surgido retos adicionales como la toxicidad de los medicamentos (4,5), el fracaso del tratamiento debido a un cumplimiento inadecuado (6,7), la resistencia a los medicamentos antirretrovirales (8) con el consecuente cambio en el esquema de tratamiento, y un incremento en la morbilidad y la mortalidad no asociadas al HIV (9,10). Los pacientes con HIV requieren un seguimiento clínico prolongado para vigilar la progresión de la enfermedad y determinar el momento oportuno para iniciar el tratamiento y para evaluar la respuesta terapéutica, el cumplimiento del tratamiento antirretroviral y los efectos secundarios, y para abordar los aspectos de salud sexual y las necesidades de prevención del HIV (11).…”
unclassified